2008
DOI: 10.1124/mol.107.042499
|View full text |Cite
|
Sign up to set email alerts
|

Kavalactones Protect Neural Cells against Amyloid β Peptide-Induced Neurotoxicity via Extracellular Signal-Regulated Kinase 1/2-Dependent Nuclear Factor Erythroid 2-Related Factor 2 Activation

Abstract: One hallmark of Alzheimer's disease is the accumulation of amyloid ␤-peptide (AP), which can initiate a cascade of oxidative events that may result in neuronal death. Because nuclear factor erythroid 2-related factor 2 (Nrf2) is the major regulator for a battery of genes encoding detoxifying and antioxidative enzymes via binding to the antioxidant response element (ARE), it is of great interest to find nontoxic activators of Nrf2 rendering neuronal cells more resistant to AP toxicity. Using ARE-luciferase assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 38 publications
(38 reference statements)
2
78
0
Order By: Relevance
“…Thus, SKN-1 appears functionally analogous to Nrf2, the best-studied member of the Nrf family, which controls phase II detoxification response genes and is centrally involved in cellular responses to oxidative stress (reviewed in Osburn and Kensler 2008). Nrf2 activation, either by tert-butylhydroquinone treatment or viral Nrf2 gene transfection, has been shown to be protective in an APP/PS1 transgenic mouse model (Kanninen et al 2008(Kanninen et al , 2009, as well as in neuronal cells exposed to exogenous Ab (Wruck et al 2008). Interestingly, a polymorphism in the human Nrf2 gene, NFE2L2, has recently been associated with earlier AD onset (Von Otter et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, SKN-1 appears functionally analogous to Nrf2, the best-studied member of the Nrf family, which controls phase II detoxification response genes and is centrally involved in cellular responses to oxidative stress (reviewed in Osburn and Kensler 2008). Nrf2 activation, either by tert-butylhydroquinone treatment or viral Nrf2 gene transfection, has been shown to be protective in an APP/PS1 transgenic mouse model (Kanninen et al 2008(Kanninen et al , 2009, as well as in neuronal cells exposed to exogenous Ab (Wruck et al 2008). Interestingly, a polymorphism in the human Nrf2 gene, NFE2L2, has recently been associated with earlier AD onset (Von Otter et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation of a human hepatic cell line with the well estabished Nrf2 activators methysticin (18) and sulforaphane (21) leads to a significant enhanced IL-6 secretion (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…18. pIL6-luc651 or pIL6-luc651⌬ARE reporter plasmids and pRL-TK plasmids (Promega) were cotransfected into HepG2-cells.…”
Section: Methodsmentioning
confidence: 99%
“…C. elegans SKN-1 is the functional orthologue of the mammalian protein Nrf2 (nuclear factor-E2-related factor 2), controlling the induction of multiple genes involved in detoxification and antioxidant stress response (Kahn et al, 2008). Nrf2 activation has been suggested to be protective in several neurodegenerative conditions, including neurons exposed to A␤ and a mouse model of AD (Kanninen et al, 2008(Kanninen et al, , 2009Wruck et al, 2008). It was also suggested that Nrf2 induction can be modulated by copper (Calay et al, 2010;Wang et al, 2010;Simmons et al, 2011).…”
Section: Copper Treatment Delays A␤-induced Paralysis In a Temperaturmentioning
confidence: 99%